Interior fixed points of unit-sphere-preserving Euclidean maps - Nirattaya Khamsemanan (2018)
Schirmer proved that there is a class of smooth self-maps of the unit sphere in Euclidean n-space with the property that any smooth self-map of the unit ball that extends a map of that class must have at least one fixed point in the interior of the ball. We generalize Schirmer's result by proving that a smooth self-map of Euclidean n-space that extends a self-map of the unit sphere of that class must have at least one fixed point in the interior of the unit ball. © 2012 Khamsemanan et al.; licensee Springer.